Ta'ib Mehmed Çelebi ve Divanı - Doğan, Güler. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2003., 2003)
This thesis aims at presenting the Turkish Divan by Taib Mehmed Çelebi who lived in the 17th century and wrote poetry in the Indian Style. Our study will establish the text of Divan, his only known work, dwell on its form, content and style, and also provide information on his life and literary personality. Taib was from Istanbul and worked as a scribe at the Imperial Council. He was a student of Naili who was a representative of the Indian Style in Ottoman lands. In fact we have two texts of Divan in relation to Taib Mehmed. One of them, which is our main source of study, is a complete divan that is wrongly attributed in the published manuscript catalogue to Osmanzade Taib Ahmed (1136/1723). The second incomplete divan is attributed in various works to the same person. We have established that the first work belongs to Taib Mehmed, while the second consists of poems by Taib Mehmed as well as another poet from the 18th century. In the present work, Divan is examined in terms of form, content and style. In terms of form, statistical information is provided about the poetry forms, meter, rhyme and redif and then an assessment is made. The content is studied in two parts, namely religious and historical-mythological elements. In the section on religious elements, the terminology related to God is cited; the quoted or alluded Qoranic verses and Prophetic Traditions are enumerated with their references and translations; and lastly, the prophets and religious events mentioned in the text are specified. As for the historical-mythological elements, brief information is given on historical and mythological events and personalities as well as on where and how they appear in the text. Finally, in the section on style, stylistic and linguistic characteristics of Divan are discussed and also examples are provided for proverbs, phrases and literary arts employed.In the conclusive part are our conclusions reached through a study of the poet's life and his Divan. At the end of the thesis, an index of compound words and adjectives as well as a copy of the text of Divan are appended.
Keywords: Turkish literature -- 17th century.; Turkish poetry.